Remittance and Economic Development in Nigeria - Nwagu, Umunna Godson; Amedu, Amos Nnaemeka (Journal of Economics Education and Entrepreneurship, 2023)
The study examined the impact of remittances on economic development in Nigeria between 1980 and 2020. ARDL (Auto-regressive Distributed Lag) is used in this study. An analysis of the unit root test was conducted in which variables such as gross domestic product per capita, gross fixed capital formation and as well as inflation, which is integrated with order zero I(0), and variables such as exchange rate, household consumption expenditure and remittances are integrated of order one I(1). In order to confirm the long-term relationships among the variables, the Co-integration bound test was used. Long-term relationships were confirmed between the variables. In addition, the study was free of serial correlations and stable. The study revealed that a positive relationship exists between remittances, gross fixed capital formation and household consumption expenditure to gross domestic product per capital (economic development) and a negative relationship between real exchange rate and gross domestic product per capital. Based on the findings of the study, it was concluded that remittances have a positive impact and are linked to economic development in the long run, and that remittances should be encouraged as an alternative means of financing investment.